2018
DOI: 10.1080/02791072.2018.1508791
|View full text |Cite
|
Sign up to set email alerts
|

The Texture of Psychoactive Illicit Drugs in Iran: Adulteration with Lead and other Active Pharmaceutical Ingredients

Abstract: Psychoactive illicit drugs are widely used all over the world. Due to the high demand for illicit drugs, adulteration of substances with poisonous and active pharmaceutical ingredients is a common phenomenon in some countries. Lead and other active pharmaceutical ingredients are among adulterants added to illicit drugs intentionally. In the present study, we analyzed four major abused street drugs in Iran's drug black market (opium, Iranian crack, ecstasy tablets, and crystal methamphetamine) to assess active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The literature search yielded 35 studies ( Table 1 ) on seized cocaine ( n = 20), opioids ( n = 14), amphetamine-like stimulants ( n = 8), NPS ( n = 2), and THC ( n = 2). Although most manuscripts considered one adulterated drug, different substance classes were investigated in 7 studies [ 12 , 13 , 14 , 15 , 16 , 17 ]. Cocaine was the most frequently adulterated drug, whereas the highest number of adulterants were detected in amphetamine-like stimulants that were adulterated with 22 different substances [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded 35 studies ( Table 1 ) on seized cocaine ( n = 20), opioids ( n = 14), amphetamine-like stimulants ( n = 8), NPS ( n = 2), and THC ( n = 2). Although most manuscripts considered one adulterated drug, different substance classes were investigated in 7 studies [ 12 , 13 , 14 , 15 , 16 , 17 ]. Cocaine was the most frequently adulterated drug, whereas the highest number of adulterants were detected in amphetamine-like stimulants that were adulterated with 22 different substances [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account the above factors researchers also critically reflected on their own experiences of working in culturally responsive contexts both within research and in the Australian AOD sector to consider some of potential nuances of the study's design. Secondary resources related to Iranian men and migratory push factors to the global north (see Khosravi 2009; Salehi-Isfahani 2011; Sekechi 2018), an understanding of some of the patterns of AOD use and related harms within Iran (Aghababaei et al 2018;Akhgari et al 2018;Khajehkazemi et al 2013;IHRA 2008, p. 13;Shariatirad et al 2013;Vazirian et al 2005) recent migration patterns (ABS 2016) and review of the complex interplay of migration and resettlement stressors for people from refugee backgrounds to Australia (see Coello 1994, 2004) were discussed amongst researchers.…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to automobile exhaust, industrial emissions, and contaminated foods through ingestion, inhalation, and dermal contacts are the known causes of chronic and acute lead poisoning. [12] In the majority of cases, lead-exposed individuals are industrial workers dealing with lead-containing materials. [1] Complications resulting from excess lead exposure mainly include hematologic and liver problems.…”
Section: Introductionmentioning
confidence: 99%
“…[16] As for Iran, Aghaee-Afshar et al [7] have proven the presence of noticeable amount of lead in illegal opium samples which may be added to the opium by drug smugglers to increase its weight. Akhgari et al [2] confirmed the presence of lead in opium, heroin, ecstasy tablets, and crystal methamphetamine in Iran. Regarding its geographical position, Iran is a major rout of opium trafficking worldwide and opium is the most common abused substance in the country.…”
Section: Introductionmentioning
confidence: 99%